To solve the system of equations:
We will use the method of substitution.
From the first equation, we can solve for x in terms of y:
6x - 3y = -6
6x = 3y - 6
x = (3y - 6)/6
x = (y - 2)/2
Now we substitute this value of x into the second equation:
9x - 3y = -18
9((y - 2)/2) - 3y = -18
(9y - 18)/2 - 3y = -18
(9y - 18 - 6y)/2 = -18
(3y - 18)/2 = -18
3y - 18 = -36
3y = -36 + 18
3y = -18
y = -18/3
y = -6
We substitute this value of y back into either equation to solve for x:
6x - 3(-6) = -6
6x + 18 = -6
6x = -6 - 18
6x = -24
x = -24/6
x = -4
Therefore, the solution to the system of equations is x = -4, y = -6.
solve the system of equations.
6x-3y=-6
9x-3y=-18
3 answers
solve the system of equations
5x-4y=-44
-x+3y=22
5x-4y=-44
-x+3y=22
To solve the system of equations:
We will use the method of substitution.
From the second equation, we can solve for x in terms of y:
-x + 3y = 22
x = 3y - 22
Now we substitute this value of x into the first equation:
5x - 4y = -44
5(3y - 22) - 4y = -44
15y - 110 - 4y = -44
11y - 110 = -44
11y = -44 + 110
11y = 66
y = 66/11
y = 6
We substitute this value of y back into the second equation to solve for x:
-x + 3(6) = 22
-x + 18 = 22
-x = 22 - 18
-x = 4
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 6.
We will use the method of substitution.
From the second equation, we can solve for x in terms of y:
-x + 3y = 22
x = 3y - 22
Now we substitute this value of x into the first equation:
5x - 4y = -44
5(3y - 22) - 4y = -44
15y - 110 - 4y = -44
11y - 110 = -44
11y = -44 + 110
11y = 66
y = 66/11
y = 6
We substitute this value of y back into the second equation to solve for x:
-x + 3(6) = 22
-x + 18 = 22
-x = 22 - 18
-x = 4
x = -4
Therefore, the solution to the system of equations is x = -4 and y = 6.